Fundamentals of corporate finance - Stephen A. Ross (McGraw-Hill Education, 2024)
The Eleventh Edition continues the tradition of excellence that has earned Fundamentals of Corporate Finance its status as market leader. McGraw-Hill's adaptive learning component, LearnSmart, provides assignable modules that help students master chapter core concepts and come to class more prepared.